Plasma and ion beam surface modification at Lawrence Berkeley National Laboratory - Brown, I. (Вопросы атомной науки и техники, 2000)
Surface processing by metal plasma and ion beams can be effected using the dense metal plasma formed in a vacuum arc discharge embodied either in a “metal plasma immersion” configuration or as a vacuum arc ion source. In the former case the substrate is immersed in the plasma and repetitively pulse-biased to accelerate the ions across the sheath and allow controlled ion energy implantation + deposition, and in the latter case a high energy metal ion beam is formed and ion implantation is done in a more-or-less conventional way. These complementary ion processing techniques provide the plasma tools for doing ion surface modification over a very wide range of ion energy, from an IBAD-like method at energies from a few tens of eV to a few keV, through ion mixing at energies in the ~1 to ~100 keV range, to 'pure' ion implantation at energies of up to several hundred keV. New hybrid processing schemes that combine the different ion energy regimes can also be explored and used in a single fabrication / modification process to make novel surfaces of complex design. Some of the applications to which we've put these plasma and ion beam tools include, for metal plasma immersion processing: doped diamond-like carbon (dlc), novel multilayers, alumina and more complex ceramic materials such as mullite (3Al₂O₃.2SiO₂), high temperature superconducting films, biomedical compatibility, and more; and for high energy ion implantation: metallurgical wear resistance, surface resistivity tailoring of ceramics, rare-earth doping of III-V compounds, and more. Here we review the fundamentals of the techniques, describe the plasma and ion beam hardware that has been developed, and outline some examples of the materials applications to which we’ve put the methods.